NEED ANALYSIS FOR PROBLEM BASED LEARNING E-COMIC ON EARTH AND SOLAR SYSTEM TOPIC - Harmelani, Giska; Putri, Azza Nuzullah; Putri, Rahmah Evita; Azhar, Aulia; Oktavia, Rani (Pendidikan IPA, FMIPA, UNP, 2024)
The aim of this study was to analyse the need for the development of science e-comic as learning media on earth and solar system topic. This research was conducted in 3 junior high schools in Sutera sub-district, based on the results of observations it is known that the school applies the kurikulum merdeka, and uses lecture and discussion methods in the learning process. However, there are obstacles that must be faced by teachers, namely the current package books/printed books are quite limited, so students have enough difficulty if they want to repeat learning material at home. This type of research is Research and Development (R&D) using the 4-D development model. This research instrument consists of a validation questionnaire, a practicality questionnaire, and an effectiveness questionnaire. The data obtained were analyzed using a formula to analyze the results of the validity test, practicality test, and effectiveness test. Based on the above problems, researchers found the right and appropriate media to be developed and can be used easily by students and teachers, namely problem-based science e-comic learning media on earth and solar system material.